Perceptions of cognitive science majors toward online learning at Universiti Malaysia Sarawak - Nur Hazirah, Binti Abu Seman (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study aims to identify the perceptions of Cognitive Science Majors toward Online Learning at Universiti Malaysia Sarawak. Online learning has become an increasingly popular learning strategy in higher education institutions due to the rapid growth of Internet technologies in Malaysia. It has been integrated in many university programs, and is one of the new learning trends that challenge of education. This study focuses on the individual's perception investigation of online learning in universities as an effective learning tool. First, this study helps identify whether students perceive usefulness and ease of use toward using online learning. This study also identifies the attitudes of students towards using the online learning. An attempt is made to analyse if attitudinal beliefs such as perceived ease of use and perceived usefulness have any relationship towards the online learning adoption.